Electric dipole polarizability of ^{40}Ca - R. W. Fearick; P. von Neumann-Cosel; S. Bacca; J. Birkhan; F. Bonaiti; I. Brandherm; G. Hagen; H. Matsubara; W. Nazarewicz; N. Pietralla; V. Yu. Ponomarev; P.-G. Reinhard; et al. (Physical Review Research, 2023)
The electric dipole strength distribution in ^{40}Ca between 5 and 25 MeV has been determined at RCNP, Osaka, from proton inelastic scattering experiments at very forward angles. Combined with total photoabsorption data at higher excitation energy, this enables an extraction of the electric dipole polarizability α_{D}(^{40}Ca)=1.92(17) fm^{3}. Together with the measured α_{D} in ^{48}Ca, it provides a stringent test of modern theoretical approaches, including coupled-cluster calculations with chiral effective field theory interactions and state-of-the art energy density functionals. The emerging picture is that for this medium-mass region dipole polarizabilities are well described theoretically, with important constraints for the neutron skin in ^{48}Ca and related equation of state quantities.